The values are:
g(-4) = -3
g(-1) = -1
g(3) = 0.5
Here's how to find g(-4), g(-1), and g(3) for the given function:
g(-4):
Since -4 is not equal to -1, we use the first part of the function definition: g(x) = -1/2 x^2 + 5.
Plug in x = -4: g(-4) = -1/2 * (-4)^2 + 5 = -1/2 * 16 + 5 = -8 + 5 = -3.
g(-1):
In this case, x is equal to -1, and we use the second part of the function definition: g(x) = -1.
Therefore, g(-1) = -1.
g(3):
Again, x is not equal to -1, so we use the first part of the function definition: g(x) = -1/2 x^2 + 5.
Plug in x = 3: g(3) = -1/2 * 3^2 + 5 = -1/2 * 9 + 5 = -4.5 + 5 = 0.5.
Therefore, the results are:
g(-4) = -3
g(-1) = -1
g(3) = 0.5